Therapeutic potential of bone marrow-derived mesenchymal stem cells for cutaneous wound healing - Chen, Jerry S.; Wong, Victor W.; Gurtner, Geoffrey C. (Frontiers in Immunology, 2012)
Despite advances in wound care, many wounds never heal and become chronic problems that result in significant morbidity and mortality to the patient. Cellular therapy for cutaneous wounds has recently come under investigation as a potential treatment modality for impaired wound healing. Bone marrow-derived mesenchymal stem cells (MSCs) are a promising source of adult progenitor cells for cytotherapy as they are easy to isolate and expand and have been shown to differentiate into various cell lineages. Early studies have demonstrated that MSCs may enhance epithelialization, granulation tissue formation, and neovascularization resulting in accelerated wound closure. It is currently unclear if these effects are mediated through cellular differentiation or by secretion of cytokines and growth factors. This review discusses the proposed biological contributions of MSCs to cutaneous repair and their clinical potential in cell-based therapies.